Technology about me without me: An examination of the relationship between patient-facing technology and patient experience - Geoffrey Silvera; Courtney Haun (The Beryl Institute, 2022)
To appreciate the role of electronic health records (EHRs) in achieving the goals of patient-centered care, scholars have focused primarily on the influence of EHR capabilities on clinical providers' behaviors. The objective of this study is to examine the degree to which patient-facing technology (P-Tech) in U.S. hospital EHRs are associated with patient evaluations of their care experience. A cross-sectional OLS regression is executed to examine the relationship between P-Tech and patient experience on a sample of U.S. hospitals (n=1,168) compiled via data from CMS, the American Hospital Association's (AHA) Annual Survey (2014), and the AHA Health Information Technology supplement (2014). Findings confirm a positive relationship between P-Tech and overall ratings of patient experience. In addition, the results find that P-Tech capabilities correspond to various communication pathways (Exchanging Information, Self-Management, and Administrative Actions) outlined by Street et al.1 The findings show an association between hospitals offering patient-facing EHR technologies that enable exchange of information and better patient evaluations of their care experience. As care delivery continues to explore the advancement of telehealth and telecare services, highlighting patient perspectives and appreciating that patients perceive face-to-face interactions as a complement to digital interactions will be key to the digital transformation of healthcare. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Innovation%20%26%20Technology%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens